Analisis Fenomena Urban Heat Island Berdasarkan Tutupan Lahan - Iqbal Perdana Putra; Aryo Sasmita; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The capital of each Province has development activities that increase along with increasing population density due to urbanization so that it results in reduce vegetation land. This condition causes an increase in surface temperature especially in the downtown area and triggers the Urban Heat Island (UHI) phenomenon. This study aims to analyze UHI phenomena based on surface temperature (LST) and index vegetation using a method the Soil Adjusted Vegetation Index (SAVI). Surface temperature extraction and land cover wereobtained from Landsat imagery. Based on the estimated surface temperature (LST) in 1996 the minimum temperature was 12,4oC and the maximum temperature was 25,8oC, while the average temperature was 19,1oC. in 2018 the minimum temperature is 19,2oC and the maximum temperature is 36,1oC, while the average temperature is 28,7oC.Keywords: Urban Heat Island, Surface Temperature, Normalized differentvegetation Index